The relationship between communication styles towards job performance in Jabatan Tanah & Ukur Kota Samarahan, Sarawak/ Mohamad Huzair Abu - Abu, Mohamad Huzair (2016)
This study was an attempt to find out the relationship between communication style towards job performance of employee in Jabatan Tanah & Ukur Kota Samarahan. The main objective of this study was to identify the communicaton styles among employee in Jabatan Tanah & Ukur Kota Samarahan. This study was based on 97 staffs from various department in Jabatan Tanah & Ukur Kota Samarahan that selected to be a respondent . To collect the primary data, researcher was used questionnaires. When the data collected from questionnaires, then it will analyzed using SPSS version 22. Pearson’s correlation was conducted to determine the degree of association between variables in this study. The result supports that, there are positive strong correlation and significant between assertive communication and employee’s performance. For future research, the data collection need to include various type of employees and organization.